2014
DOI: 10.3182/20140824-6-za-1003.01438
|View full text |Cite
|
Sign up to set email alerts
|

Fed-Batch Feeding Strategies for Enzymatic Biodiesel Production

Abstract: Abstract:In this work a kinetic model for the enzymatic transesterification of rapeseed oil using a solubilised lipase (Callera Trans L-Thermomyces lanuginosus) was developed from first principles. The model is based on a Ping-Pong Bi-Bi mechanism, with methanol inhibition, along with consideration of the differences in the interfacial and bulk concentrations of the enzyme. The model is then used to evaluate various feeding strategies to improve the enzymatic biodiesel production. The feeding strategies invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…We followed a methanol feeding strategy similar to the one proposed by Samukawa et al They found that they could increase the reuse of the immobilized enzyme (a clear indication of a reduction in enzyme deactivation), by keeping the methanol content in the reactor below the concentration that gave the highest initial rate of FAME production ( CH critical ) . In our previous work we found CH critical to be 0.525 Eq . We then combined the model of the system (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed a methanol feeding strategy similar to the one proposed by Samukawa et al They found that they could increase the reuse of the immobilized enzyme (a clear indication of a reduction in enzyme deactivation), by keeping the methanol content in the reactor below the concentration that gave the highest initial rate of FAME production ( CH critical ) . In our previous work we found CH critical to be 0.525 Eq . We then combined the model of the system (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…42 In our previous work we found CH critical to be 0.525 Eq. 43 We then combined the model of the system (Eq. 4) with the objective function in Eq.…”
Section: Uncertainty Analysis: Monte-carlo Simulationsmentioning
confidence: 99%
“…In TLL-catalyzed methanolysis reaction between crude non-degummed soybean oil and methanol, the yield of fatty acid methyl ester (biodiesel) was over 96% (w/w of oil) in the presence of 3-5% (w/w of oil) water [4]. This indicates that TLL is an efficient, convenient and soluble biocatalyst for cost-effective biodiesel production in water-requiring systems [4], [6] and [8]. Despite its great promise, the use of TLL to catalyze methanolysis reactions has its limitation because the presence of high concentrations of methanol can inactivate the enzyme [4], [5] and [8].…”
Section: Introductionmentioning
confidence: 90%
“…Enzymatic biodiesel production with lipases has attracted broad attention from both academia and industry since it offers an environmentally friendly condition with simplified separation and purification processes compared to the chemical production of biodiesel [1], [2], [3] and [4]. Recently, lipase from ascomycetous fungus Thermomyces lanuginosus (TLL) has been explored for enzymatic biodiesel production due to its high methanolysis activity [5], [6], [7] and [8]. In TLL-catalyzed methanolysis reaction between crude non-degummed soybean oil and methanol, the yield of fatty acid methyl ester (biodiesel) was over 96% (w/w of oil) in the presence of 3-5% (w/w of oil) water [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we devised and validated a mechanistic model describing the transesterification of rapeseed oil using a liquid lipase . However, when the model is used for prediction of an optimal methanol feeding profile, the model showed poor prediction of the FFA concentration in the latter half of the reaction compared with the measured FFA value.…”
Section: Introductionmentioning
confidence: 99%